Solid electrolytic capacitor and manufacturing method

By forming a conductive layer on the cathode foil and setting a foil capacitance, and using conductive polymers in the electrolyte layer, the high ESR problem caused by the conductive layer on the cathode foil is solved, and a low ESR effect in the high frequency band is achieved.

CN119790478APending Publication Date: 2025-04-08NIPPON CHEMI CON CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380062669.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the case where the conductive layer is formed on the cathode foil, the equivalent series resistance (ESR) of the solid electrolytic capacitor is higher, especially in the high frequency band, which affects the performance of the capacitor.

Method used

By forming a conductive layer on the cathode foil and including conductive polymers in the electrolyte layer, the foil capacitance of the cathode foil is set to be 20 μF/cm2 or more, and an uncontacted area is formed in part or all deep part of the etching pit to reduce ESR.

Benefits of technology

Effectively reduce ESR, especially in the 100kHz frequency band, significantly improving the performance of solid electrolytic capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790478A_ABST
    Figure CN119790478A_ABST
Patent Text Reader

Abstract

Provided is a solid electrolytic capacitor having low ESR even when a conductive layer is formed on a cathode foil. A solid electrolytic capacitor includes an anode body having a dielectric film, a cathode body, and an electrolyte layer interposed between the anode body and the cathode body. The cathode body includes a cathode foil including a valving metal, and a conductive layer formed on the cathode foil. The electrolyte layer contains a conductive polymer and is in contact with at least the conductive layer. The cathode foil has a foil capacitance of 20 [mu] F / cm2 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolytic capacitor which contains a conductive polymer in an electrolyte, obtains electrostatic capacitance by dielectric polarization of a dielectric film, and performs charge storage and discharge, and a manufacturing method thereof. Background Art

[0002] Solid electrolytic capacitors are passive components that store and discharge electric charge through electrostatic capacitance. Solid electrolytic capacitors include valve metals such as tantalum or aluminum as anode and cathode. A dielectric film is formed on the surface of the anode. An electrolyte layer is present between the anode and cathode. The electrolyte layer is in close contact with at least the dielectric film of the anode and functions as a true cathode.

[0003] Conductive polymers are sometimes used as solid electrolytes. Solid electrolytic capacitors containing conductive polymers as electrolytes have the characteristics of being small, having large capacitance, and having low equivalent series resistance, as well as being easy to form chips and suitable for surface mounting. Therefore, solid electrolytic capacitors containing conductive polymers as electrolytes are indispensable for miniaturization, high functionality, and low cost of electronic devices. In recent years, as conductive polymers, poly(3,4-ethylenedioxythiophene) (PEDOT) has been used, which has excellent adhesion to dielectric films and can increase electrostatic capacitance.

[0004] Here, the solid electrolytic capacitor is regarded as a capacitor in which the electrostatic capacitance of the anode body and the electrostatic capacitance of the cathode body are connected in series. In the above case, by making the electrostatic capacitance of the cathode body asymptotically infinite, the electrostatic capacitance of the solid electrolytic capacitor is equal to the electrostatic capacitance of the anode body, and the electrostatic capacitance of the solid electrolytic capacitor can be further improved. Therefore, there is a technical solution: by evaporating a metal nitride on the surface of the cathode foil, a metal nitride layer is formed on the surface of the cathode foil, and the metal nitride is connected to the valve metal of the cathode foil (for example, refer to Patent Document 1).

[0005] In addition, since a metal film can form fine irregularities to increase the surface area and obtain a large electrostatic capacitance, a proposal has been proposed to form a metal film on the surface of the cathode foil by vapor deposition instead of etching the cathode foil (for example, see Patent Document 2).

[0006] However, in recent years, in solid electrolytic capacitors that use conductive polymers and electrolytes as electrolytes, a scheme that includes both etching pits and inorganic conductive layers has also been proposed (for example, refer to Patent Document 3). If the inorganic conductive layer is formed in a manner that reaches the inside of the etching pit of the cathode foil, the surface of the inorganic conductive layer will also have bumps and depressions that imitate the bumps and depressions of the cathode foil. The convex part of the inorganic conductive layer contacts the conductive polymer, inhibiting the entry of the electrolyte. The electrolyte penetrates into the concave part of the inorganic conductive layer. As a result, the equivalent series resistance (ESR) of the solid electrolytic capacitor is reduced by inhibiting the decrease in the adhesion between the conductive polymer and the inorganic conductive layer and inhibiting the increase in interface resistance.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Laid-Open No. 2000-114109

[0010] Patent document 2: Japanese Patent Laid-Open No. 59-167009

[0011] Patent Document 3: International Publication No. 2016 / 174806 Summary of the invention

[0012] Problems to be solved by the invention

[0013] Figure 1 It is a logarithmic graph showing the relationship between ESR and frequency. Figure 1 As shown in the logarithmic curve shown by the dotted line, it is ideal that the ESR in the capacitive region before the self-resonance frequency decreases slowly as the frequency increases. As for the ESR, the higher the frequency band, the more blunt the decrease relative to the frequency. The relationship between ESR and frequency is flattened to the self-resonance frequency.

[0014] However, if a conductive layer is formed on the cathode foil and the conductive polymer of the electrolyte layer is attached to the conductive layer, the relationship between the ESR and the frequency changes, and a peak region 1 is generated as shown in the logarithmic curve shown by the solid line. In the frequency region above 1kHz, the ESR is blunted relative to the degree of decrease in frequency. Moreover, in the low-frequency band much lower than the self-resonant frequency, the relationship between the ESR and the frequency is close to flat. After the approximately flat region continues, the degree of decrease in the ESR relative to the frequency becomes sharper, and the degree of decrease in the ESR relative to the frequency becomes blunted and flat again until the self-resonant frequency.

[0015] The decrease in ESR with respect to the frequency is temporarily blunted, the relationship between ESR and frequency is close to flat, and the region where the decrease in ESR with respect to frequency is sharply increased again is the peak region 1. Under the premise of the presence of the conductive layer and the conductive polymer on the cathode foil, when various conditions are added, the peak region 1 is significantly manifested.

[0016] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a solid electrolytic capacitor having low ESR even when a conductive layer is formed on a cathode foil, and a method for manufacturing the same.

[0017] Technical means of solving problems

[0018] The inventors of the present invention have made great efforts to study and have obtained the following insights: the resistance Rp is generated in the cathode body due to the contact between the conductive layer and the conductive polymer. Theoretically, the resistance Rp generates the peak region 1 in the relationship between ESR and frequency, and increases the ESR in the capacitive region including the 100kHz band except for below 1kHz. Furthermore, the inventors of the present invention have made further efforts to study and have obtained the following insights: the peak region 1 is reduced by generating an electrostatic capacitance Cp in parallel with the resistance Rp, especially if the electrostatic capacitance Cp is set to 20μF / cm 2 If the value is above 0.05, the reduction in the peak region 1 extends to the 100 kHz band, and the ESR is reduced.

[0019] Therefore, in order to solve the above-mentioned problem, the solid electrolytic capacitor of the present embodiment is formed based on the above-mentioned knowledge, and comprises: an anode body, comprising a valve metal, and having a dielectric film; a cathode body, comprising a cathode foil comprising a valve metal, and a conductive layer formed on the cathode foil; and an electrolyte layer, interposed between the anode body and the cathode body, comprising a conductive polymer in contact with at least the conductive layer, and the cathode foil having a dielectric film of 20 μF / cm 2 Foil capacitors above.

[0020] The cathode foil may include an etching layer including etching pits and a dielectric film formed on the foil surface. The cathode foil capacitance is set to 20 μF / cm based on the cathode foil expansion ratio based on the etching layer and the thickness of the dielectric film. 2 That’s all.

[0021] It is also possible to have an area not in contact with the conductive layer in a part or all of the deep part of the etching pit. In the area not in contact with the conductive layer, the conductive polymer may be in contact with the cathode foil instead. On the other hand, the inventors and others have conducted diligent research and have confirmed that if there is a conductive polymer and a conductive layer of the cathode body and there is the non-contact area, the peak area 1 in the relationship between ESR and frequency increases and becomes significant. Moreover, in the case of the non-contact area, if the foil capacitance of the cathode foil is set to 20μF / cm 2 If the value is above 1, the reduction in peak region 1 will obviously extend to the 100kHz band, and the ESR will be significantly reduced.

[0022] The conductive layer may be a vapor-deposited layer that is in contact with at least the cathode foil. When the conductive layer is a vapor-deposited layer, a region that is not in contact with the conductive layer is easily generated in a part or all of the deep part of the etching pit.

[0023] The conductive layer may include titanium carbide. The conductive layer including titanium carbide has a conductivity of 20 μF / cm 2 The combination of cathode foil over foil capacitors greatly reduces ESR.

[0024] The electrolyte layer can be formed by attaching the conductive polymer in the solution or dispersion of the conductive polymer. The inventors and others have conducted diligent research and have confirmed that if there is a conductive polymer and a conductive layer of the cathode body and the conductive polymer is attached using a solution or dispersion of the conductive polymer, the peak area 1 in the relationship between ESR and frequency increases and becomes significant. Moreover, in the case where there is the non-contact area, if the foil capacitance of the cathode foil is set to 20μF / cm 2 If the value is above 1, the reduction in peak region 1 will obviously extend to the 100kHz band, and the ESR will be significantly reduced.

[0025] The cathode foil may have a strength of 250 μF / cm 2 In addition, if the capacitor is 500μF / cm 2 The expansion ratio of the etching layer as in the foil capacitor shown below reduces the possibility that the increase in ESR due to the embrittlement of the cathode foil will weaken the effect of reducing the peak region 1.

[0026] The electrolyte layer may contain an electrolyte. If the electrolyte is present, the peak area 1 is smaller than that in the absence of the electrolyte. By setting the foil capacitance of the cathode foil to 20 μF / cm 2 The above can easily make the ESR low.

[0027] The electrolyte solution may contain 25 wt % or more of ethylene glycol based on the entire solvent of the electrolyte solution.

[0028] The solvent in the electrolyte may be composed of γ-butyrolactone and sulfolane.

[0029] In order to solve the above-mentioned problem, the manufacturing method of the solid electrolytic capacitor of the present embodiment includes: a cathode body forming step, in which a foil containing a valve metal and having a capacitance of 20 μF / cm 2 A cathode body is formed by forming a conductive layer on the cathode foil; and an electrolyte layer forming step is formed between the anode body having a dielectric film and the cathode body, and the electrolyte layer includes a conductive polymer in contact with at least the conductive layer.

[0030] Effects of the Invention

[0031] According to the present invention, the ESR of a solid electrolytic capacitor including a cathode body having a conductive layer formed thereon can be suppressed to be low. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] [ Figure 1 ] is a logarithmic graph showing the relationship between ESR and frequency.

[0033] [ Figure 2 ] is a schematic diagram showing a cross section of the cathode body.

[0034] [ Figure 3 ] is a logarithmic curve graph showing the measured results of the relationship between ESR and frequency in Example 2 and Example 5.

[0035] [ Figure 4 ] is a graph showing the relationship between cathode foil capacitance and ESR when the conductive layer is TiC series and TiN series. DETAILED DESCRIPTION

[0036] Hereinafter, embodiments of the electrode foil and the electrolytic capacitor of the present invention will be described in detail. In addition, the present invention is not limited to the embodiments described below.

[0037] (Overall structure)

[0038] A solid electrolytic capacitor is a passive component that obtains electrostatic capacitance through the dielectric polarization of a dielectric film and performs charge storage and discharge. The solid electrolytic capacitor includes an anode body and a cathode body with a dielectric film formed on the surface. The anode body and the cathode body are arranged facing each other. In order to prevent the anode body and the cathode body from short-circuiting, a partition is present between the anode body and the cathode body. The anode body and the cathode body have, for example, a strip-shaped foil shape, and are wound in a circular manner with the partition sandwiched and the strip length direction.

[0039] The electrolyte layer is in close contact with at least a portion of the dielectric film of the anode body, and is interposed between the anode body and the cathode body. The electrolyte layer contains a conductive polymer. The conductive polymer is a self-doping conjugated polymer doped by an intramolecular dopant or a conjugated polymer doped by an external dopant molecule. By configuring the conductive polymer to be connected between the dielectric film and the cathode body, an electrostatic capacitance on the anode side formed by the anode body, the dielectric film and the conductive polymer is generated.

[0040] (Conductive polymer)

[0041] Conjugated polymers are obtained by chemical oxidation polymerization or electrolytic oxidation polymerization of monomers or derivatives thereof having π conjugated double bonds. As conjugated polymers, known conjugated polymers can be used without particular limitation. For example, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, polythiophenevinylene, etc. can be listed. These conjugated polymers can be used alone, or two or more can be combined, and further can be copolymers of two or more monomers.

[0042] Among the conjugated polymers, a conjugated polymer obtained by polymerizing thiophene or its derivatives is preferred, and a conjugated polymer obtained by polymerizing 3,4-ethylenedioxythiophene (i.e., 2,3-dihydrothieno[3,4-b][1,4]dioxin), 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, or derivatives thereof is preferred. As a thiophene derivative, a compound selected from thiophenes having substituents at the 3- and 4-positions is preferred, and the substituents at the 3- and 4-positions of the thiophene ring can form a ring together with the carbons at the 3- and 4-positions. The number of carbon atoms in the alkyl or alkoxy group is preferably 1 to 16.

[0043] In particular, a polymer of 3,4-ethylenedioxythiophene called EDOT, that is, poly(3,4-ethylenedioxythiophene) called PEDOT is preferred. In addition, a substituent may be added to 3,4-ethylenedioxythiophene. For example, an alkylated ethylenedioxythiophene to which an alkyl group having 1 to 5 carbon atoms is added as a substituent may be used. Examples of the alkylated ethylenedioxythiophene include methylated ethylenedioxythiophene (i.e., 2-methyl-2,3-dihydro-thieno〔3,4-b〕〔1,4〕dioxin), ethylated ethylenedioxythiophene (i.e., 2-ethyl-2,3-dihydro-thieno〔3,4-b〕〔1,4〕dioxin), butylated ethylenedioxythiophene (i.e., 2-butyl-2,3-dihydro-thieno〔3,4-b〕〔1,4〕dioxin), and 2-alkyl-3,4-ethylenedioxythiophene.

[0044] The dopant or external dopant molecule is an acceptor that easily accepts electrons from the conjugated polymer or a donor that easily gives electrons to the conjugated polymer, thereby the conductive polymer exhibits high conductivity. The dopant can be any known dopant without particular limitation. The dopant can be used alone or in combination of two or more. In addition, a polymer or a monomer can also be used.

[0045] For example, the dopant includes inorganic acids such as polyanions, boric acid, nitric acid, and phosphoric acid; and organic acids such as acetic acid, oxalic acid, citric acid, tartaric acid, squaric acid, rhodizonic acid, croconic acid, salicylic acid, p-toluenesulfonic acid, 1,2-dihydroxy-3,5-benzenedisulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, borodisalicylic acid, bisoxalylboric acid, sulfonylimide acid, dodecylbenzenesulfonic acid, propylnaphthalenesulfonic acid, and butylnaphthalenesulfonic acid.

[0046] The polyanion is, for example, a substituted or unsubstituted polyalkylene, a substituted or unsubstituted polyalkenylene, a substituted or unsubstituted polyimide, a substituted or unsubstituted polyamide, or a substituted or unsubstituted polyester, and examples thereof include a polymer containing only a structural unit having an anionic group, and a polymer containing a structural unit having an anionic group and a structural unit not having an anionic group. Specifically, examples of the polyanion include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacrylic acid sulfonic acid, polymethacrylic acid sulfonic acid, poly(2-acrylamide-2-methylpropanesulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, polymethacrylic acid, and polymaleic acid.

[0047] (Cathode)

[0048] The conductive polymer is also in contact with the cathode body. Here, the cathode body includes a cathode foil and a conductive layer. The conductive layer is stacked on one side or both sides of the cathode foil and is located on the outermost layer of the cathode body. If the conductive polymer is in contact with the conductive layer of the cathode body, resistance Rp is generated on the cathode body side. The resistance Rp is not limited to this, and it is speculated that it is the contact resistance between the conductive polymer and the conductive layer, the volume resistance, and the contact resistance between the conductive layer and the cathode foil. The resistance Rp of the cathode body generates a peak region 1 in the relationship between ESR and frequency. That is, except for below 1kHz, in the capacitive region including the 100kHz frequency band, the ESR is increased.

[0049] If an electrostatic capacitance Cp is generated in parallel with the resistor Rp, the expansion of the peak region 1 can be suppressed. Therefore, an electrostatic capacitance Cp is also generated on the cathode body side. However, the electrostatic capacitance Cp on the cathode body side does not asymptotically approach infinity, and the electrostatic capacitance of the solid electrolytic capacitor becomes a composite capacitance of the anode side and the cathode side.

[0050] In order to generate electrostatic capacitance Cp in the cathode body, the cathode foil is expanded through an etching layer formed by a plurality of pits to form a dielectric film. The cathode foil is a long foil body formed by extending the valve metal. The valve metal is aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth and antimony. Regarding the purity, the cathode body is ideally 99% or more, and may also contain silicon, iron, copper, magnesium, zinc, etc.

[0051] The etching layer includes tunnel-shaped pits or sponge-shaped pits. Tunnel-shaped etching pits are holes dug in the thickness direction of the foil. The tunnel-shaped pits can be used to penetrate the foil, or they can be formed by a length that does not reach the center of the foil. The tunnel-shaped etching pits are typically formed by passing a direct current through an acidic aqueous solution such as hydrochloric acid in which halogen ions exist. The tunnel-shaped etching pits are further expanded by passing a direct current through an acidic aqueous solution such as nitric acid. Through the sponge-shaped etching pits, the expanded layer becomes a sponge-shaped layer that is expanded by connecting fine gaps into a space. The sponge-shaped etching pits are formed by passing an alternating current through an acidic aqueous solution such as hydrochloric acid in which halogen ions exist.

[0052] The dielectric film is formed on the concavo-convex surface of the etching layer. The dielectric film is typically an oxide film formed on the concavo-convex surface of the expansion layer. For example, if the cathode foil is made of aluminum, it is an aluminum oxide layer that oxidizes the concavo-convex surface of the expansion layer. In the chemical conversion treatment for forming the dielectric film, a voltage is applied to the cathode foil in a chemical conversion solution. The chemical conversion solution is a solution without halogen ions, for example, a phosphoric acid-based chemical conversion solution such as ammonium dihydrogen phosphate, a boric acid-based chemical conversion solution such as ammonium borate, and an adipic acid-based chemical conversion solution such as ammonium adipate.

[0053] Alternatively, the dielectric film may be oxide particles different from those of the cathode foil, and may be formed on the concave and convex surface of the etching layer using a vapor phase film forming method or a liquid phase film forming method. As the vapor phase film forming method, a chemical vapor method (chemical vapor deposition (CVD)) or a physical vapor method (physical vapor deposition (PVD)) may be cited, and as the liquid phase film forming method, plating or coating may be cited.

[0054] Thus, the cathode foil has a 20 μF / cm 2 The foil capacitance is the electrostatic capacitance of the cathode foil. The foil capacitance of the cathode foil is set to the following value: two test pieces of a specified area are cut out from the cathode foil, the two test pieces are placed facing each other, and the two test pieces are immersed in the electrostatic capacitance measurement liquid in the glass measurement tank, and the value is twice the value measured using the electrostatic capacitance meter. For example, the specified area is 1cm 2The electrostatic capacitance measuring liquid was set to an aqueous solution of ammonium adipate at 30° C., the electrostatic capacitance meter was set to an inductance capacitance resistance (LCR) meter, and as measurement conditions, the AC amplitude was set to 0.5 Vms and the measurement frequency was set to 120 Hz.

[0055] To achieve 20μF / cm 2 The above foil capacitance is adjusted by adjusting the cathode foil expansion rate based on the etching layer, and adjusting the thickness of the dielectric film by applying voltage. That is, according to C = εS / d, by increasing the expansion rate, the surface area is increased, the foil capacitance is increased, and by making the dielectric film thinner, the foil capacitance is increased, and the foil capacitance is adjusted to 20μF / cm 2 above.

[0056] Alternatively, a natural oxide film formed by the reaction of the cathode foil with oxygen in the air may be used instead of the dielectric film. In this case, the surface expansion factor is specifically adjusted to 20 μF / cm 2 above.

[0057] If the cathode foil capacitance is 20 μF / cm 2 Above, the expansion of the peak region 1 decreases, and the ESR of the solid electrolytic capacitor decreases in each frequency band. In particular, if the cathode foil capacitance is 20 μF / cm 2 On the other hand, if the cathode foil capacitance is less than 20 μF / cm 2 , the overall reduction degree of the peak region 1 is small, and the ESR reduction rate in the high-frequency band including the 100kHz band is low.

[0058] The larger the cathode foil capacitance is, the more the peak region 1 is eliminated from the low frequency level, and the ESR starts to decrease from the low frequency level. The cathode foil capacitance is preferably 500 μF / cm 2 Below, particularly preferably 250 μF / cm 2 Below. Below 250μF / cm 2 The expansion of the peak region 1 has been corrected to approach the ideal ESR curve under the foil capacitance of 500μF / cm, and sufficient ESR reduction is achieved in the 100kHz band in particular. On the other hand, if the foil capacitance of the cathode foil exceeds 500μF / cm 2 , in order to increase the surface area, the etching layer needs to be deepened, and the remaining core of the cathode foil becomes thinner. The remaining core is the area that the etching layer does not reach. If the remaining core becomes thinner, the strength of the cathode foil decreases. Due to the decrease in the strength of the cathode foil, there is a possibility that cracks or pores will occur in the cathode foil, and cracks or pores will weaken the ESR reduction effect caused by eliminating the peak area 1.

[0059] The conductive layer can be formed on the cathode foil on which the etching layer and the dielectric film are formed. As the conductive layer, it is sufficient as long as it mainly contains an inorganic substance or an inorganic compound having a higher conductivity than the dielectric film of the cathode foil. The conductive layer can be stacked in multiple layers, and each layer can also be a layer containing different types of inorganic compounds. The thickness of the conductive layer is preferably 50nm or more.

[0060] The inorganic substance or inorganic compound contained in the conductive layer can be mainly composed of inorganic substances or inorganic compounds, and may contain organic functional groups such as carboxyl groups or mixtures, such as carbon black. Examples of the inorganic substance or inorganic compound include titanium, zirconium, tantalum, niobium, nitrides or carbides of these, aluminum carbide, carbon raw materials, and composite materials or mixed materials of these. Examples of the carbon raw material include fibrous carbon, carbon powder, or a mixture of these.

[0061] Carbon powders include, for example, natural plant tissues such as palm shells, synthetic resins such as phenol, activated carbon derived from fossil fuels such as coal, coke, asphalt, etc., carbon blacks such as Ketjen black, acetylene black, channel black, carbon nanohorns, amorphous carbon, natural graphite, artificial graphite, graphitized Ketjen black, mesoporous carbon, etc. Fibrous carbon includes, for example, carbon nanotubes, carbon nanofibers, etc. Carbon nanotubes may be single-layer carbon nanotubes in which a graphene sheet is one layer, or multi-layer carbon nanotubes (MWCNT) in which two or more graphene sheets are coaxially rounded and the tube wall is formed with multiple layers.

[0062] The inorganic compound contained in the conductive layer is preferably titanium carbide, which is titanium carbide. In the case of forming a conductive layer containing titanium carbide, if the foil capacitance of the cathode foil is less than 20 μF / cm 2 , the peak region 1 expands greatly as a whole, and the ESR of the solid electrolytic capacitor increases. However, when a conductive layer containing titanium carbide is formed, if the foil capacitance of the cathode foil is 20 μF / cm 2 Above, the peak region 1 is suddenly eliminated well, and the ESR of the solid electrolytic capacitor is greatly reduced.

[0063] The conductive layer can be attached to the cathode foil by coating, evaporation or heat treatment. The coating method is to apply a slurry containing an inorganic substance or an inorganic compound, a binder and a solvent to the cathode foil by a slurry casting method, a doctor blade method or a spray method, and dry it, and if necessary, press the cathode foil to make it close to the conductive layer. The evaporation method can be vacuum arc evaporation, sputtering evaporation or electron beam evaporation. The heat treatment makes the powder of the inorganic substance or inorganic compound adhere to the surface of the cathode foil and sinter it.

[0064] Vacuum arc evaporation is to apply voltage to the material source in a vacuum chamber to melt and evaporate it, so that the evaporated material source reacts with the reaction gas, and the material source that reacts with the reaction gas is formed on the cathode foil. Sputtering evaporation is to generate plasma in an environment where a target is configured and filled with a reaction gas, knock out the material source from the target, and make the knocked-out material source react with the reaction gas, and form a film of the material source that reacts with the reaction gas on the cathode foil. Electron beam evaporation irradiates the material source with an electron beam in a vacuum chamber to melt and evaporate it, so that the evaporated material source reacts with the reaction gas, and the material source that reacts with the reaction gas is formed on the cathode foil.

[0065] Figure 2 is a schematic diagram showing a cross section of the cathode body. Figure 2 As shown, when forming the conductive layer, it is preferred that a region not in contact with the conductive layer region 31 as the region of the conductive layer, that is, a non-contact region 22 as a non-contact region is generated in a part or all of the deep part of the pit 21 of the etching layer. In the pit 21, the cathode side dielectric film 33 is also formed in the non-contact region 22. The conductive polymer particles enter the non-contact region 22 instead of the conductive layer region 31, and the conductive polymer region 32 as the region of the conductive polymer can also be in contact with the cathode side dielectric film 33.

[0066] Therefore, it is preferable to form the conductive layer in such a manner that even if the conductive polymer or the electrolyte can penetrate into the pits 21, the pits 21 are not blocked in the conductive layer region 31. Alternatively, it is preferable to form the conductive layer in such a manner that even if the openings of the pits 21 are blocked in the conductive layer region 31, the conductive polymer or the electrolyte can penetrate into the pits 21 through the conductive layer region 31. For example, the particle size of the inorganic substance or inorganic compound is increased or the density is adjusted so that the pores between the inorganic substance or inorganic compound constituting the conductive layer are larger than the conductive polymer or the electrolyte.

[0067] On the other hand, in the case of having a conductive layer and containing a conductive polymer in the solid electrolyte layer, if the non-contact area 22 is provided, the peak area 1 in the relationship between ESR and frequency becomes significant. That is, the degree of ESR decrease is significantly blunted, and the flat area of ​​ESR becomes longer. However, if the foil capacitance of the cathode foil is set to 20μF / cm 2 As a result, the elimination of the peak region 1 becomes significant. Therefore, the solid electrolytic capacitor including the foil having the non-contact region 22 has a capacitance of 20 μF / cm 2 The cathode foil described above is a suitable embodiment.

[0068] As a method for setting the uncontacted area 22, it is preferred to use a vapor deposition method as the basis when forming the conductive layer. Among them, compared with chemical vapor deposition, it is preferred to select physical vapor deposition. By selecting physical vapor deposition, it is difficult for particles of inorganic substances or inorganic compounds to reach the deep part of the etching layer. In addition, the etching layer is preferably formed by sponge-like pits 21. If the sponge-like pits 21 are complex hole-shaped, it is more difficult for particles of inorganic substances or inorganic compounds to reach the deep part of the etching layer. The diameter of the sponge-like pits 21 is preferably the same as or smaller than that of the inorganic substance or inorganic compound, preferably less than 1μm. It is further preferred that the diameter of the sponge-like pits 21 is 50nm to 300nm. Thereby, the possibility of inorganic substances or inorganic compounds reaching the deepest part of the sponge-like pits can be further reduced.

[0069] Furthermore, if the non-contact region 22 which is a region not in contact with the conductive layer region 31 can be formed in a part or all of the deep part of the pit 21 of the etching layer, a certain effect can be obtained. The method for forming the conductive layer is not limited to the vapor deposition method.

[0070] (Manufacturing method)

[0071] This type of solid electrolytic capacitor is manufactured in the following manner. That is, the anode body and the cathode body are respectively manufactured through the anode body forming process and the cathode body forming process. The anode body and the cathode body in the form of a foil are wound with a separator sandwiched between them to manufacture a cylindrical winding body formed by the anode foil, the cathode foil and the separator. In the electrolyte forming process, a capacitor element is formed by attaching a conductive polymer to the winding body. The capacitor element is inserted into a bottomed cylindrical outer casing, and the open end of the outer casing is sealed by riveting and using a sealing body. Then, after an aging process, the manufacture of the solid electrolytic capacitor is completed.

[0072] In the process of attaching the conductive polymer, it is preferred to adjust the conductive polymer liquid and impregnate the conductive polymer into the winding body. Regarding the solid electrolytic capacitor filled with the conductive polymer by the method of impregnating the conductive polymer liquid, the peak region 1 in the relationship between ESR and frequency is significantly generated. Therefore, the foil capacitance is 20μF / cm 2 The cathode body described above is a suitable embodiment.

[0073] The conductive polymer liquid has conductive polymer particles or powder dispersed or dissolved therein. The wound body is impregnated with the conductive polymer liquid, and the solvent is at least partially volatilized by drying, so that the conductive polymer is attached to the anode body and the cathode body.

[0074] Conductive polymers are produced by electrolytic polymerization or chemical polymerization. In chemical polymerization, a solution containing monomers that become monomer units of conductive polymers is mixed with an oxidant and subjected to polymerization reaction. As an oxidant, if it is a compound that releases a dopant, it can be any known one, and trivalent iron salts such as iron (III) p-toluenesulfonate, iron (III) naphthalenesulfonate, and iron (III) anthraquinonesulfonate, or peroxodisulfate salts such as peroxodisulfuric acid, ammonium peroxodisulfate, and sodium peroxodisulfate can be used. A single compound can be used, or two or more compounds can be used. There is no strict restriction on the polymerization temperature, but it is generally in the range of 10°C to 200°C. The polymerization time is generally in the range of 10 minutes to 30 hours.

[0075] In the electrolytic polymerization, the monomers that will become the monomer units of the conductive polymer are mixed with a supporting electrolyte and the polymerization reaction is carried out by a constant potential method, a constant current method or a potential scanning method. The supporting electrolyte contains at least one compound selected from the group consisting of borodisalicylic acid and borodisalicylate. As salts, there can be exemplified: alkali metal salts such as lithium salts, sodium salts, potassium salts, ammonium salts, alkylammonium salts such as ethylammonium salts and butylammonium salts, dialkylammonium salts such as diethylammonium salts and dibutylammonium salts, trialkylammonium salts such as triethylammonium salts and tributylammonium salts, tetraalkylammonium salts such as tetraethylammonium salts and tetrabutylammonium salts.

[0076] In the case of the constant potential method, the potential is preferably 1.0 V to 1.5 V with respect to the reference electrode, and in the case of the constant current method, it is preferably 1 μA / cm 2 ~10000μA / cm 2 The current value is preferably scanned at a rate of 5 mV / sec to 200 mV / sec in the range of 0 V to 1.5 V relative to the reference electrode when a potential scanning method is used. The polymerization temperature is not strictly limited, but is generally in the range of 10°C to 60°C. The polymerization time is generally in the range of 10 minutes to 30 hours.

[0077] In electrolytic polymerization and chemical polymerization, the solvent of the monomer and the oxidant or the supporting electrolyte can dissolve the desired amount of monomer and supporting electrolyte, and the solvent that does not adversely affect the electrolytic polymerization can be used without particular limitation. For example, as a solvent, water, methanol, ethanol, isopropanol, butanol, ethylene glycol, acetonitrile, butyronitrile, acetone, methyl ethyl ketone, tetrahydrofuran, 1,4-dioxane, γ-butyrolactone, methyl acetate, ethyl acetate, methyl benzoate, ethyl benzoate, ethylene carbonate, propylene carbonate, nitromethane, nitrobenzene, cyclopentane, dimethyl cyclopentane. These solvents can be used alone or in combination of two or more.

[0078] After the conductive polymer is produced, the conductive polymer liquid is prepared by purifying the solution after electrolytic polymerization or chemical polymerization by ultrafiltration, cation exchange, anion exchange, etc., removing residual monomers and impurities, and dispersing or dissolving them in the solution.

[0079] The solvent of the conductive polymer liquid can be any solvent that disperses or dissolves the conductive polymer, and is preferably water or a mixture of water and an organic solvent. Examples of the organic solvent include polar solvents, alcohols, esters, hydrocarbons, carbonate compounds, ether compounds, chain ethers, heterocyclic compounds, and nitrile compounds.

[0080] As polar solvents, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, etc. can be listed. As alcohols, methanol, ethanol, propanol, butanol, etc. can be listed. As esters, ethyl acetate, propyl acetate, butyl acetate, etc. can be listed. As hydrocarbons, hexane, heptane, benzene, toluene, xylene, etc. can be listed. As carbonate compounds, ethylene carbonate, propylene carbonate, etc. can be listed. As ether compounds, dioxane, diethyl ether, etc. can be listed. As chain ethers, ethylene glycol dialkyl ethers, propylene glycol dialkyl ethers, polyethylene glycol dialkyl ethers, polypropylene glycol dialkyl ethers, etc. can be listed. As heterocyclic compounds, 3-methyl-2-oxazolidinone, etc. can be listed. As nitrile compounds, acetonitrile, glutaronitrile, methoxyacetonitrile, propionitrile, benzonitrile, etc. can be listed.

[0081] The pH of the conductive polymer liquid can be adjusted, and polyols and various additives can be added as needed. As pH adjusters, for example, ammonia water, sodium hydroxide, primary amines, secondary amines, and tertiary amines can be cited. As polyols, sorbitol, ethylene glycol, diethylene glycol, triethylene glycol, polyoxyethylene glycol, glycerol, polyglycerol, polyoxyethylene glycerol, xylitol, erythritol, mannitol, dipentaerythritol, pentaerythritol, or a combination of two or more of these can be cited. Since the boiling point of polyols is high, even after the conductive polymer liquid is impregnated in the attachment object and dried, it will remain in the electrolyte layer, and the ESR reduction or withstand voltage improvement effect of the electrolytic capacitor can be obtained. As additives, for example, organic binders, surfactants, dispersants, defoamers, coupling agents, antioxidants, ultraviolet absorbers, etc. can be cited.

[0082] When the solvent is removed by a drying process, the temperature environment in the drying process is, for example, above 40°C and below 200°C, and the drying time is, for example, in the range of above 3 minutes and below 180 minutes. The drying process can be repeated multiple times. It can also be dried under a reduced pressure environment, for example, under a pressure of above 5 kPa and below 100 kPa. The drying process can be divided into a pre-drying process and a formal drying process. In addition to dipping, the conductive polymer solution can also be applied by dropwise coating or spray coating.

[0083] Alternatively, the conductive polymer may be formed in the electrolytic capacitor by immersing the wound body in a solution of a monomer, which is a monomer unit of the conductive polymer, and an oxidant or a supporting electrolyte and generating the wound body by a polymerization reaction.

[0084] An electrolyte may also be added to the electrolyte layer. The electrolyte layer contains a conductive polymer and an electrolyte, and the electrolyte is filled in a manner that fills the gap between the dielectric film and the conductive polymer. The electrolyte is a mixed solution in which a solute is dissolved in a solvent and an additive is added as needed. The electrolyte may not contain a solute and may be only a solvent, or may be a mixed solution of a solvent and an additive.

[0085] As the solvent of the electrolyte, protic organic polar solvents or aprotic organic polar solvents can be listed, which can be used alone or in combination of two or more. In addition, as the solute of the electrolyte, an anion component or a cationic component is included. The solute is typically a salt of an organic acid, a salt of an inorganic acid, or a salt of a composite compound of an organic acid and an inorganic acid, which can be used alone or in combination of two or more. It is also possible to add an acid as an anion and a base as a cation to the solvent, respectively.

[0086] Examples of protic organic polar solvents as solvents include monohydric alcohols, polyhydric alcohols, and oxyhydric alcohol compounds. Examples of monohydric alcohols include ethanol, propanol, butanol, pentanol, hexanol, cyclobutanol, cyclopentanol, cyclohexanol, and benzyl alcohol. Examples of polyhydric alcohols and oxyhydric alcohol compounds include ethylene glycol, propylene glycol, glycerol, polyglycerol, methyl cellosolve, ethyl cellosolve, methoxypropylene glycol, dimethoxypropanol, polyethylene glycol, polyoxyethylene glycerol, and other polyhydric alcohol alkylene oxide adducts.

[0087] As a non-protonic organic polar solvent of the solvent, sulfone series, amide series, lactone series, cyclic amide series, nitrile series, sulfoxide series, etc. can be listed as representatives. As sulfone series, dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, cyclopentane, 3-methylcyclopentane, 2,4-dimethylcyclopentane, etc. can be listed. As amide series, N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-diethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-ethylacetamide, N,N-diethylacetamide, hexamethylphosphoramide, etc. can be listed. As lactone series and cyclic amide series, γ-butyrolactone, γ-valerolactone, δ-valerolactone, N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, isobutylene carbonate, etc. can be listed. As nitrile series, acetonitrile, 3-methoxypropionitrile, glutaronitrile, etc. can be listed. Examples of the sulfoxide-based compounds include dimethyl sulfoxide and the like.

[0088] Among them, the solvent is preferably ethylene glycol or glycerol. Ethylene glycol and glycerol cause changes in the higher-order structure of the conductive polymer, and the initial ESR characteristics are good, and thus the high-temperature characteristics also become good. In particular, due to the changes in the higher-order structure of the conductive polymer in the pits of the cathode foil and the conductive polymer near the conductive layer, the adhesion between the conductive polymer and the conductive layer is improved and the capacitance extraction effect of the cathode foil becomes larger, and the initial ESR characteristics become good. It is better if ethylene glycol is 25wt% or more in the solvent. If ethylene glycol accounts for more than 25wt% in the solvent, other solvents such as γ-butyrolactone or cyclopentane sulfone may also be included.

[0089] When γ-butyrolactone or sulfolane is used as the solvent, it is preferred to use a solvent composed of γ-butyrolactone and sulfolane rather than a solvent composed of only γ-butyrolactone or a solvent composed of only sulfolane. When a solvent composed of both γ-butyrolactone and sulfolane is used, the ESR of the solid electrolytic capacitor decreases compared to a solvent composed of only γ-butyrolactone or a solvent composed of only sulfolane.

[0090] Examples of organic acids that serve as anion components as solutes include carboxylic acids such as oxalic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, heptanoic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, tridecanedicarboxylic acid, tert-butyladipic acid, 11-vinyl-8-octadecenedicarboxylic acid, resorcinolic acid, pyrogallolic acid, gallic acid, gentisic acid, protocatechuic acid, catecholcarboxylic acid, trimellitic acid, and pyromellitic acid, or phenols and sulfonic acids.

[0091] Inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid. Composite compounds of organic acids and inorganic acids include boron disalicylic acid, boron dioxalic acid, boron diglycolic acid, boron dimalonic acid, boron disuccinic acid, boron diadipic acid, boron diazelaic acid, boron dibenzoic acid, boron dimaleic acid, boron dilactic acid, boron dimalic acid, boron ditartaric acid, boron dicitric acid, boron diphthalic acid, boron di(2-hydroxy)isobutyric acid, boron diresorcinolic acid, boron dimethylsalicylic acid, boron dinaphthoic acid, boron dimandelic acid, and boron di(3-hydroxy)propionic acid.

[0092] In addition, as at least one salt of an organic acid, an inorganic acid, and a composite compound of an organic acid and an inorganic acid, for example, ammonium salts, quaternary ammonium salts, quaternary amidinium salts, amine salts, sodium salts, potassium salts, etc. Examples of quaternary ammonium ions of quaternary ammonium salts include tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. Examples of quaternary amidinium include ethyldimethylimidazolinium, tetramethylimidazolinium, etc. Examples of amine salts include salts of primary amines, secondary amines, and tertiary amines. Examples of primary amines include methylamine, ethylamine, propylamine, etc. Examples of secondary amines include dimethylamine, diethylamine, ethylmethylamine, dibutylamine, etc. Examples of tertiary amines include trimethylamine, triethylamine, tributylamine, ethyldimethylamine, ethyldiisopropylamine, etc.

[0093] Furthermore, other additives may also be added to the electrolyte. As additives, alkylene oxide adducts of polyols such as polyethylene glycol or polyoxyethylene glycerol, complex compounds of boric acid and polysaccharides (mannitol, sorbitol, etc.), complex compounds of boric acid and polyols, boric acid esters, nitro compounds (o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, p-nitrobenzyl alcohol, etc.), phosphates, etc. These may be used alone or in combination of two or more. The amount of additive added is not particularly limited, and it is preferably added to a degree that does not deteriorate the characteristics of the solid electrolytic capacitor, for example, the electrolyte is less than 30wt%.

[0094] In the above solid electrolytic capacitor, the anode body is also a foil body formed by extending the valve metal, and the purity is ideally 99.9% or more. A surface expansion layer is formed on one or both sides of the foil of the anode body. In addition to being an etching layer, the surface expansion layer can also be a sintered layer formed by sintering the powder of the valve metal, or a vapor-deposited layer formed by vapor-depositing the particles of the valve metal. As methods of sintering and vapor deposition, atomic layer deposition or vapor deposition, powder sintering and lamination forming methods, etc. can be listed. That is, in addition to being set as tunnel-shaped pits or sponge-shaped pits, the surface expansion layer can also be set as a porous structure containing dense powders or gaps between particles. A dielectric film is formed on the concave and convex surface of the surface expansion layer of the anode body by chemical conversion treatment, vapor phase film formation or liquid phase film formation.

[0095] The separator can be made of kraft paper, Manila hemp, esparto, hemp, cellulose such as rayon, and mixed paper thereof, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof, polytetrafluoroethylene resins, polyvinylidene fluoride resins, vinylon resins, polyamide resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides, polyimide resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and polyvinyl alcohol resins, and these resins can be used alone or in combination. However, if the short circuit between the anode and cathode can be prevented and the conductive polymer and the electrolyte can be maintained, the separator can be eliminated.

[0096] Solid electrolytic capacitors may also be laminated types in which an electrolyte layer and a cathode body are laminated on an anode body on a flat plate. In the laminated type, in addition to being a flat plate type without an outer package, the capacitor element may be sealed by, for example, covering it with a laminate film or molding, dipping or printing a resin such as a heat-resistant resin or an insulating resin.

[0097] (Effect)

[0098] Ideally, the ESR in the capacitive region before the self-resonance frequency decreases slowly as the frequency increases in a logarithmic graph. The ESR decreases more slowly with respect to the frequency in the higher frequency band. The relationship between ESR and frequency is flattened to the self-resonance frequency.

[0099] However, if a conductive layer is formed on the cathode foil and the conductive polymer of the electrolyte layer is attached to the conductive layer, the relationship between the ESR and the frequency changes, and a peak region 1 is generated. In the frequency region above 1kHz, the ESR is blunted relative to the degree of decrease in frequency. Moreover, in the low-frequency band much lower than the self-resonant frequency, the relationship between the ESR and the frequency is close to flat. After the approximately flat region continues, the degree of decrease in the ESR relative to the frequency becomes sharper, and the degree of decrease in the ESR relative to the frequency becomes blunted and flat again until the self-resonant frequency.

[0100] The decrease in ESR relative to the frequency is temporarily passivated, the relationship between ESR and frequency is close to flat, and the region where the decrease in ESR relative to frequency is sharply increased again is the peak region 1. If there is a non-contact region 22 where the conductive layer is not in contact with a part or all of the deep part of the etching pit, the peak region 1 is significantly manifested. That is, the decrease in ESR is significantly passivated, and the flat region of ESR becomes longer. In addition, if a conductive polymer liquid is used to form an electrolyte layer of a conductive polymer, the peak region 1 is significantly manifested. In addition, the peak region 1 is significantly manifested in a solid electrolytic capacitor that does not use an electrolyte.

[0101] Next, the impedance of the cathode foil in the capacitive region before the self-resonance frequency, 1 / (2πfCp)[|Zp|], decreases in proportion to the frequency in the logarithmic graph. Furthermore, if the resistance Rp>|Zp|, the decrease in the ESR that is passivated by the generation of the peak region 1 can be increased. That is, the peak region 1 can be eliminated. Furthermore, the ESR up to the self-resonance frequency can be reduced as a whole.

[0102] The impedance is |Zp|=1 / (2πfCp). If the cathode foil capacitance Cp is increased, the logarithmic curve showing the relationship between the impedance and the frequency will shift in the direction of reducing the impedance as a whole, and the frequency at which the resistance Rp>|Zp| becomes lower. At a frequency of 100kHz, if it is 20μF / cm 2 As described above, the ESR reduction effect by the foil capacitance Cp of the cathode foil connected in parallel with the resistor Rp is significantly exhibited.

[0103] [Example]

[0104] Hereinafter, the solid electrolytic capacitor will be described in more detail based on examples. In addition, the present invention is not limited to the following examples.

[0105] (Example 1 to Example 5)

[0106] Solid electrolytic capacitors of Examples 1 to 5, Comparative Example 1, and Reference Examples 1 and 2 were produced as follows.

[0107] The anode foil is a strip-shaped aluminum foil extending in a long strip and having a thickness of 110 μm. The anode foil is expanded by AC etching. In forming the expanded layer of the anode foil, an AC current is passed through the aluminum foil in an aqueous solution containing hydrochloric acid, thereby forming a sponge-like etching pit. Regarding the anode body, a dielectric film is formed on the surface of the foil by chemical conversion treatment.

[0108] The cathode foil was a strip-shaped aluminum foil extending in a long strip and having a thickness of 50 μm. In order to generate 10 μF / cm2 corresponding to each solid electrolytic capacitor in the cathode foil, 2 ~250μF / cm 2 The foil capacitance Cp is formed to form an etching layer, and a dielectric film is formed on the concave and convex surface of the etching layer. An alternating current is passed through the aluminum foil in an aqueous solution containing hydrochloric acid to form an etching layer containing sponge-like etching pits. Titanium carbide TiC is stacked on each cathode foil as a conductive layer. TiC is stacked on the cathode foil with a thickness of 110nm by vacuum arc evaporation. In addition, TiC is stacked in a manner that a non-contact area 22 is generated in the deep part of the pit 21.

[0109] In the AC etching treatment of the cathode foil, the cathode foil is immersed in an acidic aqueous solution with hydrochloric acid as the main electrolyte to expand the two sides of the aluminum foil. Then, in the chemical conversion treatment of the cathode foil, after the chlorine attached during the AC etching treatment is removed by using an aqueous phosphoric acid solution, a voltage corresponding to the thickness of the dielectric film is applied in an aqueous solution of ammonium dihydrogen phosphate. The foil capacitance Cp is obtained as follows: based on the theoretical formula Cp = εS / d, the expansion ratio of the etching layer and the thickness of the dielectric film are repeatedly adjusted to achieve the desired value.

[0110] The separator is sandwiched in the middle, the strip directions of the anode body and the cathode body are aligned, the two electrodes are overlapped, and the strips are wound in a circular manner in the length direction to form a wound body. In Examples 1 to 5 and Comparative Example 1, the separator is Manila hemp. In Reference Examples 1 and 2, the separator is special nylon fiber. The prepared wound body is placed in an aqueous solution of ammonium dihydrogen phosphate at a liquid temperature of 90°C and a current density of 2.5 mA / cm is passed. 2 The current was increased to reach a chemical conversion voltage of 56 V and maintained for 15 minutes.

[0111] The conductive polymer is attached by impregnating the winding bodies of Examples 1 to 5 and Comparative Example 1 with a conductive polymer liquid. The conductive polymer liquid contains poly(3,4-ethylenedioxythiophene) (PEDOT / PSS) doped with polystyrenesulfonic acid (PSS) dispersed in water. PEDOT / PSS is added at a ratio of 1.2 wt% relative to the conductive polymer liquid as a whole. Ethylene glycol is added to the conductive polymer liquid at a ratio of 10 wt% relative to the conductive polymer liquid as a whole. The conductive polymer liquid is impregnated in the winding body for 5 minutes at room temperature and under reduced pressure. The impregnation process is performed twice in total. The winding body is dried by standing at a temperature of 150°C for 30 minutes after each impregnation process.

[0112] Conductive polymers were generated and attached to the wound bodies of Reference Examples 1 and 2 by chemical polymerization. The wound bodies were immersed in a mixed solution of 3,4-ethylenedioxythiophene monomer and iron (III) p-toluenesulfonate as an oxidant for releasing dopants, and polymerization was performed. The polymerization temperature was 150° C. and the polymerization time was 30 minutes.

[0113] In Examples 1 to 5 and Comparative Example 1, the wound body to which the conductive polymer was attached was further impregnated with an electrolyte. The electrolyte was prepared by adding ammonium azelaic acid to ethylene glycol. The solid electrolytic capacitors of Reference Examples 1 and 2 did not use an electrolyte.

[0114] Each capacitor element produced is housed in a cylindrical shell, and the opening of the cylindrical shell is sealed with a sealing body. Voltage is applied to each solid electrolytic capacitor and an aging treatment is performed. Thus, as Examples 1 to 5 and Comparative Example 1, solid electrolytic capacitors with a rated voltage of 35WV, a rated capacitance of 56μF, a diameter of 6.3mm and a height of 6.1mm are produced. In addition, as Reference Examples 1 and 2, solid electrolytic capacitors with a rated voltage of 25WV and a rated capacitance of 47μF are produced.

[0115] (ESR measurement)

[0116] The ESR of Examples 1 to 5, Comparative Example 1, and Reference Examples 1 and 2 was measured. The ESR was measured by connecting the terminals of the LCR meter to the anode body and the cathode body, and setting the ambient temperature to 20°C and the measurement frequency to 100 kHz as measurement conditions. The measurement results are shown in Table 1 below. The ESR measurement results are shown in Table 1 below together with the foil capacitance of each cathode foil. In addition, two test pieces of a specified area were cut out from the cathode foil, and the two test pieces were made to face each other and immersed in an electrostatic capacitance measurement liquid in a glass measurement tank, and measured using an electrostatic capacitance meter, and twice the value obtained was used as the foil capacitance of each cathode foil. The specified area is set to 1cm 2 The capacitance measurement liquid was set to an aqueous solution of ammonium adipate at 30° C., the capacitance meter was set to an LCR meter, and as measurement conditions, the AC amplitude was set to 0.5 Vms and the measurement frequency was set to 120 Hz.

[0117] (Table 1)

[0118]

[0119] As shown in Table 1, the ESR of the solid electrolytic capacitors of Examples 1 to 5 is suppressed to be low compared with Comparative Example 1. In the solid electrolytic capacitors of Examples 1 to 5, the foil capacitance of the cathode foil is set to 20 μF / cm 2 Especially if the cathode foil has a capacitance of 40 μF / cm 2 Above and 250μF / cm 2 In addition, when the examples are compared with the reference examples, it is confirmed that in the solid electrolytic capacitor in which the conductive polymer is attached using a conductive polymer liquid, the foil capacitance of the cathode foil is set to 20 μF / cm 2 The above mentioned ESR reduction effect is significant.

[0120] (Example 6 and Example 7)

[0121] The solid electrolytic capacitors of Examples 6 and 7 were manufactured as follows. Examples 6 and 7 differ from Examples 1 to 5 in that no electrolyte solution was used in combination. Except for the fact that no electrolyte solution was used in combination, the solid electrolytic capacitors of Examples 6 and 7 had the same structure and composition as that of Example 1 and were manufactured by the same manufacturing method and under the same conditions. The foil capacitance of the cathode foil of Example 6 was set to 150 μF / cm 2 , the foil capacitance of Example 7 is set to 20 μF / cm 2 .

[0122] (ESR measurement)

[0123] The ESR of Examples 6 and 7 was measured. The method and conditions for measuring the ESR were the same as those of Example 1. The results of the ESR measurement are shown in Table 2 below together with the foil capacitance of each cathode foil.

[0124] (Table 2)

[0125]

[0126] As shown in Table 2, in the solid electrolytic capacitors of Examples 6 and 7 without an electrolyte solution, it was also confirmed that the cathode foil capacitance was 20 μF / cm 2 As shown in Tables 1 and 2, it was confirmed that the overall ESR was lowered when the electrolyte was used in combination.

[0127] (Relationship between ESR and frequency)

[0128] While changing the measurement frequency in the range of 100 Hz to 1000 kHz, the cathode foil capacitance was measured to be 150 μF / cm 2 The solid electrolytic capacitor of Example 2 and the cathode foil have a capacitance of 20 μF / cm 2 The ESR of the solid electrolytic capacitor of Example 5 is shown in FIG. Figure 3 middle. Figure 3 It means that the cathode body includes a TiC conductive layer, a conductive polymer is attached by a conductive polymer liquid and an electrolyte is used, and the foil capacitance of the cathode foil is 150μF / cm 2 or 20μF / cm 2 A logarithmic graph of the relationship between frequency and ESR of a solid electrolytic capacitor.

[0129] exist Figure 3 In the case of foil, the capacitance Cp is 20 [μF / cm 2 ] is represented by the logarithmic curve G1, and the foil capacitance Cp is 150 [μF / cm 2 ] Example 2 is represented by a logarithmic curve G2.

[0130] like Figure 3 As shown, a peak region 1 is generated in the range of 1 kHz and above and 100 kHz. The peak region 1 is expanded and eliminated in the logarithmic curve G2 compared to the logarithmic curve G1. That is, it can be confirmed that the larger the foil capacitance Cp of the cathode foil is, the more the peak region 1 is eliminated and the more the ESR is reduced.

[0131] In addition, it can be confirmed that in the frequency band where the magnitude of the impedance 1 / (2πfCp)[|Zp|] generated by the foil capacitance Cp of the cathode foil becomes the resistance Rp>|Zp| in the logarithmic graph, the ESR changes in a manner that imitates the change in the magnitude of the impedance. Therefore, it can be confirmed that the degree of decrease in the ESR that was blunted due to the generation of the peak region 1 is greatly restored in imitation of the magnitude of the impedance. In other words, it can be confirmed that the tendency of eliminating the peak region 1 is confirmed.

[0132] The impedance is |Zp|=1 / (2πfCp). If the cathode foil capacitance Cp is increased, the frequency at which the resistance Rp>|Zp| becomes lower. At a frequency of 100kHz, if the capacitance is 20μF / cm 2 From the above, it can be confirmed that the ESR reduction effect brought about by the foil capacitance Cp of the cathode foil connected in parallel with the resistor Rp is significantly exhibited.

[0133] (Example 8 to Example 12)

[0134] The solid electrolytic capacitors of Examples 8 to 12 and Comparative Example 2 were manufactured as follows. In contrast to Examples 1 to 5 in which a conductive layer containing titanium carbide TiC was laminated on a cathode foil, the difference between Examples 8 to 12 and Comparative Example 2 is that a conductive layer containing titanium nitride TiN was laminated on the cathode foil. The solid electrolytic capacitors of Examples 8 to 12 had the same structure and composition as those of Examples 1 to 5, and were manufactured by the same manufacturing method and under the same conditions, except for the type of inorganic compound contained in the conductive layer.

[0135] The cathode foil capacitance of Example 8 is set to 250 μF / cm 2 The cathode foil capacitance of Example 9 is set to 150 μF / cm 2 The cathode foil capacitance of Example 10 is set to 50 μF / cm 2 The cathode foil capacitance of Example 11 is set to 40 μF / cm 2 The cathode foil capacitance of Example 12 is set to 20 μF / cm 2 In addition, the foil capacitance of the cathode foil of Comparative Example 2 was set to 10 μF / cm 2 .

[0136] (ESR measurement)

[0137] The ESR of Examples 8 to 12 and Comparative Example 2 was measured. The ESR measurement method and measurement conditions were the same as those of Example 1. The ESR measurement results are shown in Table 3 below together with the foil capacitance of each cathode foil. Figure 4 As shown, based on Table 3, the conductive layer is divided into TiC series and TiN series, and a graph is made with the horizontal axis being the cathode foil capacitance and the vertical axis being the ESR. Figure 4 In the figure, the drawings marked with hollow circles are the TiC series, and the drawings marked with solid circles are the TiN series.

[0138] (Table 3)

[0139]

[0140] As shown in Table 3, it was confirmed that even if the inorganic compound contained in the conductive layer was TiN, as shown in Examples 8 to 12, by making the foil capacitance of the cathode foil 20 μF / cm 2 As the value increases within the above range, the ESR of the solid electrolytic capacitor also decreases.

[0141] In addition, as shown in Table 3 and Figure 4 As shown, it was confirmed that the series of Examples 1 to 5 and Comparative Example 1 containing TiC in the conductive layer had a lower cathode foil capacitance of less than 20 μF / cm compared to the series of Examples 8 to 12 and Comparative Example 2 containing TiN in the conductive layer. 2 , then the ESR is high, but if the cathode foil capacitance is 20μF / cm 2 Above, the ESR drops sharply and is better than that of the TiN series. From this, it is confirmed that if the conductive layer contains TiN and the cathode foil capacitance is 20μF / cm 2 Above, the ESR of the solid electrolytic capacitor is particularly reduced.

[0142] (Example 13 to Example 37)

[0143] Solid electrolytic capacitors of Examples 13 to 37 and Comparative Examples 3 to 7 were prepared. The solvents of the electrolytes of Examples 13 to 37 and Comparative Examples 3 to 7 were different from those of Examples 1 to 5 and Comparative Example 1. In Examples 1 to 5 and Comparative Example 1, ethylene glycol was used as the solvent of the electrolyte.

[0144] In contrast, in Examples 13 to 17 and Comparative Example 3, the solvent consists of 25 wt% of ethylene glycol and 75 wt% of γ-butyrolactone. In Examples 18 to 22 and Comparative Example 4, the solvent consists of 10 wt% of ethylene glycol and 90 wt% of γ-butyrolactone. In Examples 23 to 27 and Comparative Example 5, the electrolyte uses γ-butyrolactone in its entirety. In Examples 28 to 32 and Comparative Example 6, the solvent consists of 50 wt% of γ-butyrolactone and 50 wt% of cyclopentane sulfone. In Examples 33 to 37 and Comparative Example 7, the solvent of the electrolyte uses cyclopentane sulfone in its entirety.

[0145] The cathode foils of Examples 13 to 17 and Comparative Example 3 have different foil capacitances. The foil capacitance of the cathode foil of Example 13 is set to 250 μF / cm 2 The cathode foil capacitance of Example 14 is set to 150 μF / cm 2 The cathode foil capacitance of Example 15 is set to 50 μF / cm 2 The cathode foil capacitance of Example 16 is set to 40 μF / cm 2 The cathode foil capacitance of Example 17 is set to 20 μF / cm 2 In addition, the foil capacitance of the cathode foil of Comparative Example 3 was set to 10 μF / cm 2 .

[0146] The cathode foils of Examples 18 to 22 and Comparative Example 4 have different foil capacitances. The foil capacitance of the cathode foil of Example 18 is set to 250 μF / cm 2 The cathode foil capacitance of Example 19 is set to 150 μF / cm 2 The cathode foil capacitance of Example 20 is set to 50 μF / cm 2 The cathode foil capacitance of Example 21 is set to 40 μF / cm 2 The cathode foil capacitance of Example 22 is set to 20 μF / cm 2 In addition, the foil capacitance of the cathode foil of Comparative Example 4 was set to 10 μF / cm 2 .

[0147] The cathode foils of Examples 23 to 27 and Comparative Example 5 have different foil capacitances. The foil capacitance of the cathode foil of Example 23 is set to 250 μF / cm 2 The cathode foil capacitance of Example 24 is set to 150 μF / cm 2 The cathode foil capacitance of Example 25 is set to 50 μF / cm 2 The cathode foil capacitance of Example 26 is set to 40 μF / cm 2 The cathode foil capacitance of Example 27 is set to 20 μF / cm 2In addition, the foil capacitance of the cathode foil of Comparative Example 5 was set to 10 μF / cm 2 .

[0148] The cathode foils of Examples 28 to 32 and Comparative Example 6 have different foil capacitances. The foil capacitance of the cathode foil of Example 28 is set to 250 μF / cm 2 The cathode foil capacitance of Example 29 is set to 150 μF / cm 2 The cathode foil capacitance of Example 30 is set to 50 μF / cm 2 The cathode foil capacitance of Example 31 is set to 40 μF / cm 2 The cathode foil capacitance of Example 32 is set to 20 μF / cm 2 In addition, the foil capacitance of the cathode foil of Comparative Example 6 was set to 10 μF / cm 2 .

[0149] The cathode foils of Examples 33 to 37 and Comparative Example 7 have different foil capacitances. The foil capacitance of the cathode foil of Example 33 is set to 250 μF / cm 2 The cathode foil capacitance of Example 34 is set to 150 μF / cm 2 The cathode foil capacitance of Example 35 is set to 50 μF / cm 2 The cathode foil capacitance of Example 36 is set to 40 μF / cm 2 The cathode foil capacitance of Example 37 is set to 20 μF / cm 2 In addition, the foil capacitance of the cathode foil of Comparative Example 7 was set to 10 μF / cm 2 .

[0150] Except for the type of the electrolyte solvent, the solid electrolytic capacitors of Examples 13 to 37 and Comparative Examples 3 to 7 have the same structure and composition as Example 1 and are manufactured by the same manufacturing method and under the same conditions.

[0151] (ESR measurement)

[0152] The ESR of Examples 13 to 37 and Comparative Examples 3 to 7 was measured. The ESR measurement method and measurement conditions were the same as those of Example 1. The ESR measurement results are shown in Tables 4 to 8 below together with the foil capacitance of each cathode foil. In the table, EG is ethylene glycol, BL is γ-butyrolactone, and TMS is cyclopentane. In the table, the value in brackets after the type of solvent is the weight percentage concentration in the solvent.

[0153] (Table 4)

[0154]

[0155] (Table 5)

[0156]

[0157] (Table 6)

[0158]

[0159] (Table 7)

[0160]

[0161] (Table 8)

[0162]

[0163] As shown in Table 1 and Table 4 above, in Examples 1 to 5 and Examples 13 to 17, the foil capacitance of the cathode foil is 20 μF / cm 2 When the ESR of the solid electrolytic capacitor is 0.033Ω, if the cathode foil capacitance is 50μF / cm 2 As shown in Table 1, Table 4 to Table 8, these ESRs are lower than those of the same cathode foil capacitors in Examples 18 to 37.

[0164] In Examples 1 to 5 and Examples 13 to 17, 25 wt % or more of ethylene glycol was contained in the solvent of the electrolyte. This confirmed that when 25 wt % or more of ethylene glycol was contained relative to the entire solvent of the electrolyte, ESR became better.

[0165] Furthermore, as shown in Tables 6 to 8, when Examples 23 to 37 are compared, it can be seen that Examples 28 to 32 have lower ESR in each foil capacitor of the cathode foil than Examples 23 to 27 and Examples 33 to 37.

[0166] In Examples 28 to 32, the solvent of the electrolyte solution consisted of both γ-butyrolactone and sulfolane. It was thus confirmed that the ESR of the solid electrolytic capacitor decreased when the solvent consisted of both γ-butyrolactone and sulfolane, compared with the case where the solvent consisted of only γ-butyrolactone or only sulfolane.

[0167] [Description of Figure Numbers]

[0168] 1: Peak area

[0169] 21: Pit

[0170] 22: Untouched area

[0171] 31: Conductive layer area

[0172] 32: Conductive polymer region

[0173] 33: Cathode side dielectric film

Claims

1. A solid electrolytic capacitor, characterized in that include: an anode body comprising a valve action metal and having a dielectric film; A cathode body including a cathode foil including a valve action metal and a conductive layer formed on the cathode foil; as well as an electrolyte layer, interposed between the anode body and the cathode body, comprising a conductive polymer at least in contact with the conductive layer, The cathode foil has a 20 μF / cm 2 Foil capacitors above.

2. The solid electrolytic capacitor according to claim 1, characterized in that: The cathode foil has: an etch layer comprising etch pits; and Dielectric film, formed on the surface of the foil.

3. The solid electrolytic capacitor according to claim 2, characterized in that: A part or all of the etching pit has a region not in contact with the conductive layer in its deep portion.

4. The solid electrolytic capacitor according to claim 3, characterized in that: The conductive layer is a vapor-deposited layer that is in contact with at least the cathode foil.

5. The solid electrolytic capacitor according to any one of claims 1 to 4, characterized in that: The conductive layer includes titanium carbide.

6. The solid electrolytic capacitor according to any one of claims 1 to 4, characterized in that: The electrolyte layer is formed by attaching the conductive polymer in a solution or dispersion of the conductive polymer.

7. The solid electrolytic capacitor according to any one of claims 1 to 4, characterized in that: The cathode foil has a 250 μF / cm 2 The following foil capacitors.

8. The solid electrolytic capacitor according to any one of claims 1 to 4, characterized in that: The electrolyte layer contains an electrolyte solution.

9. The solid electrolytic capacitor according to claim 8, characterized in that: The electrolyte solution contains 25 wt % or more of ethylene glycol based on the entire solvent of the electrolyte solution.

10. The solid electrolytic capacitor according to claim 8, characterized in that: The solvent in the electrolyte is composed of γ-butyrolactone and sulfolane.

11. A method for manufacturing a solid electrolytic capacitor, characterized in that include: The cathode body forming process includes a valve metal and a foil capacitance of 20μF / cm 2 forming a conductive layer on the cathode foil to form a cathode body; and The electrolyte layer forming step forms an electrolyte layer including a conductive polymer in contact with at least the conductive layer between the anode body having the dielectric film and the cathode body.

Citation Information

Patent Citations

  • Method of producing electrode material for electrolytic condenser

    JP1984167009A

  • Solid electrolytic capacitor and its manufacture

    JP2000114109A

  • Electrolytic capacitor

    WO2016174806A1